Samara Joy [compact disc] - Samara Joy; Grasso, Pasquale; Roland, Ari; Washington, Kenny; Pierson, Matt (Whirlwind Recordings, 2021)
Samara Joy is a singing star in ascendancy: the young vocalist attracted attention in 2019 after winning the Sarah Vaughan International Jazz Vocal Competition. Now, the 21-year-old announces her self-titled debut release, which puts her spin on jazz standards from the Great American Songbook. Produced by Grammy-nominated veteran Matt Pierson, she's joined by jazz guitar virtuoso Pasquale Grasso and his trio (Ari Roland and Kenny Washington) for a release that furthers Joy's reputation as one of America's most promising young jazz vocalists.